Perancangan ulang produk mixer dengan Metode Quality Function Deployment - Akbar Gading Alfadli Harahap; Rosnani Ginting; Aulia Ishak (Institut Seni Indonesia Yogyakarta, 2026)
The need for electronic devices has become essential for many people. Nearly all households have adopted their use in various functions and forms, which has consequently led to several issues. One such case involves mixer, an appliance specifically used in the culinary field for mixing dough. The research problem focuses on the weakening of the screw joint on the body cover due to strong vibrations and high-frequency usage. Additionally, the screw holes are too deep, making the assembly process difficult. Therefore, product design improvement is required using the Quality Function Deployment (QFD) Phase I and Phase II methods. This study aims to identify the priority of technical characteristics and critical parts in the mixer product using QFD Phase I and QFD Phase II. Technical characteristics refer to the distinctive features of the product that enable it to perform optimally, such as ease of assembly and the number of components relative to their level of complexity. The product’s critical part refers to the most essential and crucial component, namely, the body cover, which has the highest level of assembly difficulty and thus requires immediate improvement. The improvement proposed for the mixer involves changing the type of joint from the current bolt-based design to a snap-fit design, thereby reducing the number of components and assembly time for 2 units and 17,19 seconds respectively, and enhancing ease of assembly based on the efficiency design calculation by 0,56%.